Effects of Crop Insurance Premium Subsidies on Crop Acreage. (11th October 2017) - Yu, Jisang; Smith, Aaron; Sumner, Daniel A.
Abstract : Crop insurance premium subsidies affect patterns of crop acreage for two reasons. First, holding insurance coverage constant, premium subsidies directly increase expected profit, which encourages more acreage of insured crops (direct profit effect). Second, premium subsidies encourage farms to increase crop insurance coverage. With more insurance coverage, farms obtain more subsidies, and farm revenue becomes less variable as indemnities offset revenue shortfalls, so acreage of insured crops likely increases (indirect coverage effect). By exploiting exogenous policy changes and using approximately 180, 000 county‐crop‐year observations, we estimate the sum of these two effects of premium subsidies on the pattern of U.S. acreage across seven major field crops. We estimate that a 10% increase in the premium subsidy causes a 0.43% increase in the acreage of a crop in a county holding the premium subsidy of its competing crop constant. Taking into account the small share of premium subsidies in expected crop revenue, this subsidy impact is analogous to an own‐subsidy acreage elasticity of 1.24, which exceeds own‐price acreage elasticity estimates in the literature. One explanation for the larger acreage response to premium subsidies is that insurance causes an indirect coverage effect in addition to a direct profit effect.